The Bacillus subtilis dCMP deaminase ComEB acts as a dynamic polar localization factor for ComGA within the competence machinery. Issue 5 (31st January 2020) - Burghard‐Schrod, Marie; Altenburger, Stephan; Graumann, Peter L.
Abstract: Bacillus subtilis can import DNA from the environment by an uptake machinery that localizes to a single cell pole. We investigated the roles of ComEB and of the ATPase ComGA during the state of competence. We show that ComEB plays an important role during competence, possibly because it is necessary for the recruitment of GomGA to the cell pole. ComEB localizes to the cell poles even upon expression during exponential phase, indicating that it can serve as polar marker. ComEB is also a deoxycytidylate monophosphate (dCMP) deaminase, for the function of which a conserved cysteine residue is important. However, cysteine‐mutant ComEB is still capable of natural transformation, while a comEB deletion strain is highly impaired in competence, indicating that ComEB confers two independent functions. Single‐molecule tracking (SMT) reveals that both proteins exchange at the cell poles between bound and unbound in a time scale of a few milliseconds, but turnover of ComGA increases during DNA uptake, whereas the mobility of ComEB is not affected. Our data reveal a highly dynamic role of ComGA during DNA uptake and an unusual role for ComEB as a mediator of polar localization, localizing by diffusion‐capture on an extremely rapid time scale and functioning as a moonlighting enzyme. Abstract : ComEB is an enzyme involved in nucleotide metabolism, which confers a second, enzyme‐independent function during natural transformation. The ATPase ComGA, a component of the DNA uptake machinery in Bacillus subtilis, is localized to the cell pole by ComEB. Both, ComEB and ComGA, exchange rapidly between pole‐bound and freely diffusive modes. ComGA changes its residence time during DNA uptake, revealing highly dynamic kinetics during the formation of a polar multiprotein complex.